Automatisierte Wissenskommunikation - Holste, Alexander (Wissenskommunikation / Knowledge Communication AMP, 2024)
Algorithm;Specialized communication;Specialized communication research;Specialist language;Special knowledge;Information design;Information science;AI;Artificial intelligence;Cybernetics;Machine translation;Media psychology;Multilingual communication;Human-machine interaction;Neural machine translation;Rule-based machine translation;Recurrent neural networks;Statistical machine translation ;Sociology of Technology;Text-to-speech;DeepL